Assessment of accessory canals of the canalis sinuosus: a study of 1000 cone beam computed tomography examinations - Machado, V. de C.; Chrcanovic, B. R.; Felippe, M. B.; Manhaes, L. R. C. Junior [UNESP]; Carvalho, P. S. P. de [UNESP] (Churchill Livingstone, 2016)
The aim of this study was to verify the presence, spatial location, and calibre of the accessory canals (AC) of the canalis sinuosus by cone beam computed tomography, and their relationship to the anterior maxilla. This retrospective analysis included the scans of 1000 subjects. Parameters registered were sex, age, number of AC, presence or absence of AC with a diameter <1.0 mm, AC diameter (only for AC with a diameter >1.0 mm), and AC location in relation to the adjacent teeth. Males showed a statistically higher frequency of AC than females. The difference in age distribution was not statistically significant. Twenty percent of all AC presented a diameter of a least 1.0 mm. The end of the AC trajectory was most frequently located palatal to the anterior maxillary teeth. All relationships analyzed here were very weak (age vs. number of AC, age vs. AC diameter, number of AC vs. sex). Overall, the results of this study showed that AC of the canalis sinuosus are a common anatomical structure in the anterior maxilla, regardless of age and sex.
Keywords: maxilla; anterior superior alveolar nerve; canalis sinuosus; anatomical variation; morphometric measurements; cone beam computed tomography